Fitting Constrained Continuous Spline Curves. - Kong, V.P.; Ong, B. H. (2003)
Fitting a curve through a set of planar data which represents a positive quantity requires that the curve stays above the horizontal axis, The more general problem of designing parametric and non-parametric curves which do not cross the given constraint boundaries is considered. Several methods will be presented.